SEMINAR DAN DISKUSI “PERAN GENERASI MUDA DALAM MEMBANGUN EKONOMI DAERAH” DI SMA KURNIA JAYA DESA PANGKALAN NYIRIH KECAMATAN RUPAT - Devi Kurniawati; Deswarta; Rona Rona Naula Oktaviani (JURNAL PENGABDIAN MASYARAKAT: IJTIMA', 2024)
Pangkalan Nyirih Village is one of the villages in Rupat Sub-district which has the natural potential of mangrove forests, extensive agricultural and plantation fields which can be seen from the majority of the population working as farmers.. In the future, this village will be used as an Independent Integrated City Center (KTM), as seen from the construction of road and bridge facilities that facilitate access in and out of the village and other public facilities. With the potential of the village, there needs to be attention from various groups, especially the younger generation, to take the opportunity to make the potential of Pangkalan Nyirih Village more developed and economically beneficial for local residents and the environment. This service program aims to provide an overview of the potential possessed by the younger generation in Rupat to build their regional economy in the future and also aims to provide an understanding of the importance of the contribution of the younger generation and the opportunities that are very open in taking the opportunity to build the regional economy, especially Pangkalan Nyirih Village. The results of the implementation of this service are expected to open insights, provide provisions and motivation to students as a young generation in taking the next step after completing the study period at Kurnia Jaya High School to enthusiastically achieve their goals, be able to capture business opportunities and improve the regional economy to be more advanced in the future.